2010
DOI: 10.1007/s11096-010-9372-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adverse drug reactions through the minimum basic data set

Abstract: The MBDS is a useful and accessible instrument to determine the incidence of ADR in a hospital, resulting in the notification of severe events that might otherwise not be reported. Its use also improves identification of the main drugs responsible for ADR and of the patient populations at greatest risk, facilitating the implementation of alert systems and the development of prevention and detection strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…There was an increase in the number of ADE from 11 007 in 2004 to 18 750 in 2013 (global rate 1.46%). In Europe, studies using administrative databases have shown that the rate of adverse drug reactions are between 0.8% - 1.83% [11, 13, 26]. The systematic review of Cano et al about the ADE in hospitals found that the proportion of patients with ADEs ranged from 2.15% to 19.2% in Europe [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an increase in the number of ADE from 11 007 in 2004 to 18 750 in 2013 (global rate 1.46%). In Europe, studies using administrative databases have shown that the rate of adverse drug reactions are between 0.8% - 1.83% [11, 13, 26]. The systematic review of Cano et al about the ADE in hospitals found that the proportion of patients with ADEs ranged from 2.15% to 19.2% in Europe [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the rate of ADR in hospital inpatients ranging from 0.8% to 26.1% [711]. Also it was found that 1.8% to 12.8% of ADR can lead to hospitalization [12–15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the rate of ADR in hospital inpatients ranging from 0.8% to 26.1% [79, 36, 37]. Studies using administrative datasets have shown rates of ADR between 0.8% and 1.8% in Europe [26, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using administrative datasets have shown rates of ADR between 0.8% and 1.8% in Europe [26, 37, 38]. The differences in the results observed can be due to differences in the accuracy of data reporting in the datasets used or to the definition of the ADR.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse drug reactions (ADRs) are a significant cause of morbidity and mortality and contribute to a substantial burden on the public health system with significant financial costs. In Australia alone, it has been estimated that almost two million patients suffer an adverse drug event annually with 190 000 requiring hospitalisation . Spontaneous reporting systems (SRS) are an effective mechanism for detecting ADRs and form an essential part of post‐marketing drug surveillance .…”
Section: Introductionmentioning
confidence: 99%